2020
DOI: 10.7554/elife.54508
|View full text |Cite
|
Sign up to set email alerts
|

Spen links RNA-mediated endogenous retrovirus silencing and X chromosome inactivation

Abstract: The Xist lncRNA mediates X chromosome inactivation (XCI). Here we show that Spen, an Xist-binding repressor protein essential for XCI , binds to ancient retroviral RNA, performing a surveillance role to recruit chromatin silencing machinery to these parasitic loci. Spen loss activates a subset of endogenous retroviral (ERV) elements in mouse embryonic stem cells, with gain of chromatin accessibility, active histone modifications, and ERV RNA transcription. Spen binds directly to ERV RNAs that show structural s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 59 publications
3
45
0
Order By: Relevance
“…Also worth noting was that most exFVtgrs contained stop codons and their ORFs were incomplete, which might have indicated that they were likely to be ERV-derived long noncoding RNAs (lncRNAs) rather than exogenous retroviruses. Moreover, they might also function as lncRNAs to participate in genomic regulatory processes (56)(57)(58). However, this speculation should be verified by further study.…”
Section: Discussionmentioning
confidence: 96%
“…Also worth noting was that most exFVtgrs contained stop codons and their ORFs were incomplete, which might have indicated that they were likely to be ERV-derived long noncoding RNAs (lncRNAs) rather than exogenous retroviruses. Moreover, they might also function as lncRNAs to participate in genomic regulatory processes (56)(57)(58). However, this speculation should be verified by further study.…”
Section: Discussionmentioning
confidence: 96%
“…Recently, it has been shown that depletion of Spen reactivates a subset of ERVs in mouse ESCs. Spen has been found to bind to ERV-derived RNA and recruited several chromatin remodeling factors such as histone deacetylases [116]. Another example for RNA-mediated regulation of ERVs is the Piwi-interacting RNA (piRNA) pathway.…”
Section: Rna-mediated Targeting Of Tesmentioning
confidence: 99%
“…Finally, it is now possible to successfully create synthetic lncRNAs. By adding RNA shapes to carefully chosen RNA templates, investigators are starting to create designer lncRNAs that can regulate chromatin in vivo 100 , suffice to partly rescue the physiological lncRNA gene knockout 102 , or target RNAs to specific cytotopic locations within the cell 103 , 104 .…”
Section: Long Non-coding Rnas: a Time To Buildmentioning
confidence: 99%